Benchmarking Heavy Metal Contamination For Brownfield in Malaysia - Lee, A.; Nikraz, Hamid; Hung, Y. (World Scientific Press, 2009)
Malaysia has over 10,000 brownfield sites which have yet to be registered. In fact there is limited information and controls on soil and groundwater contamination from these brownfield sites. In this study, four brownfield sites were examined in terms of the soil and groundwater quality to benchmark the heavy metal contents to be used as indicators of soil and groundwater contamination and to derive suggested benchmarking reference for remedial action to be taken. It also described briefly the possible remediation techniques to clean up the heavy metals in brownfield sites and the need for registration of brownfield sites towards sustainable development.